Review article: long‐term safety of nucleoside and nucleotide analogues in HBV‐monoinfected patients. Issue 1 (19th May 2016) - Lampertico, P.; Chan, H. L. Y.; Janssen, H. L. A.; Strasser, S. I.; Schindler, R.; Berg, T.
Summary: Background: Nucleos(t)ide analogues (NUCs) for chronic hepatitis B treatment achieve high rates of viral suppression and are generally well tolerated. Entecavir (ETV) and tenofovir disoproxil fumarate (TDF) are the currently preferred first‐line agents. The safety of these agents in clinical practice is particularly relevant since long‐term treatment is usually required. Aim: To summarise and critically discuss recent real‐world evidence on the safety of treatment with ETV or TDF in hepatitis B virus (HBV)‐monoinfected patients. Methods: PubMed and conference proceedings up to 15th June 2015 were searched using the terms ((((Hepatitis_B) OR HBV) AND ((tenofovir) OR entecavir)) AND (((lactic_acidosis) OR bone) OR renal)). Results: In selected populations included in registration studies, both ETV and TDF were well tolerated with no clinically significant renal toxicity or lactic acidosis. Growing 'real‐world' clinical experience with these agents includes some reports of ETV‐associated lactic acidosis and TDF‐associated renal impairment; however, evidence from cohort studies appears to be conflicting. In the case of ETV‐related lactic acidosis, a small number of cases have been reported, all in patients with decompensated cirrhosis. The degree of association between TDF treatment and changes in markers of renal function varies between studies: discrepancies may result from the use of different definitions and cut‐offs for reporting renal toxicities, and differences in patient populations. Conclusions: Pre‐treatment and on‐treatment monitoring of eGFR and phosphorus, with prompt appropriate dose adjustment or treatment switch can minimise the impact of NUC renal toxicity. Standardisation of measures of renal impairment and identification of early molecular markers remain an unmet need.